Optimizing the mirror illusion during mirror therapy: evidence from unimpaired individuals - Kim, Jin Min; Challis, Freya O.; Koo, Carmen C. Y.; Leung, Jade-Cheuk L.; Lo, Leo H.; Yeo, Sang-Hoon; Punt, T. David (Frontiers in Psychology, 2025)
IntroductionMirror therapy has demonstrated functional benefits for patients recovering from hemiparetic stroke, with its effectiveness primarily attributed to the induction of a compelling visual illusion that engages sensorimotor networks. Although previous research has identified various intervention parameters influencing therapeutic outcomes, a comprehensive understanding of their effects on the illusory experience remains limited. This study investigated how four critical parameters—mirror size (large vs. small), object manipulation (present vs. absent), task complexity (simple vs. complex), and movement execution (unilateral vs. bilateral)—modulate the believability of the mirror illusion in neurologically unimpaired individuals.MethodsForty healthy participants performed movements under 16 different combinations of these parameters while receiving mirror visual feedback and rated the believability of the reflected hand on an 11-point Likert scale.ResultsRepeated-measures ANOVA revealed that a large mirror consistently enhanced the illusory experience compared to a small mirror. Although bimanual movements generally resulted in higher believability ratings than unimanual movements, this advantage diminished when complex object manipulation tasks were introduced.DiscussionThese findings suggest that the congruency of multisensory information—between visual, proprioceptive, and motor signals—is critical for maximising the strength of the illusory experience. By identifying the optimal conditions for enhancing the mirror illusion in healthy individuals, this study establishes a foundational framework for adapting and refining mirror therapy protocols in clinical populations.